The ideological dimension in the novel Fadel Gamal Qaisi - Alqaisi, Wijdan (Al-Adab Journal, 2024)
This study seeks to identify the ideologies that the author tries to include in his literary text with full awareness of him, or what leaks from the ideologies possessed by the author appear in the novel's body without awareness of him and the ideological dimension of the novel shows "communication" through the ideologies of the characters and the ideology of the narrator, and this novel is not just a subject of entertainment only, but ideology should be an artistic and aesthetic element and its relationship with reality through the principle of ideological pluralism.